The Morale of Supervision: The Impact of Technical Supervision Skills of Teaching and Learning on Teachers’ Self-Efficacy - Dzahir Kasa, Muhamad; Hibatul Hakimie Mahmood, Mohd; Faiz Mohd Yaakob, Mohd; Rahimi Yusof, Mat; Omar-Fauzee, M.S.; Khun-Inkeeree, Hareesol; Rashidah Mohd Sofian, Fatimah Noor (International Journal of Criminology and Sociology, 2022)
The Minister of Education Malaysia specifically issues Circular 3/1987, which notes that it is the responsibility of the principal or director to practice his position as a supervisor in the management of the teaching and learning process in the classroom. This is show that the importance of supervisory processes. However, oversight can be assigned to senior assistants in the case of any obstacle to its execution. The consistency of monitoring is frequently contested because of several issues and vulnerabilities. Recognizing the importance of supervisory processes to enhance teacher professionalism, this study was conducted to examine the influence of teaching and learning supervision and teacher self-efficacy. This research was conducted among 211 teachers who engaged in the teaching and learning supervision process in 13 primary schools chosen by the Jeli District Education Office, Kelantan. The questionnaire was used to gather data and information. The study also indicates that the dimension of professional supervision skills has the greatest effect on the instructor's self-efficiency. In brief, the evaluation of teaching and learning cannot be overlooked, because the findings of the study suggest that these factors have to do with the self-efficacy of the teacher, and cannot be discounted as a factor in the performance of the school.